Integration of Toba Batak Local Wisdom as Character and Multicultural Education Values in the Curriculum - Sitorus, Masniar H.; Barasa, Tiurma; Sihaloho, Martua; Manik, Sonia Shindy A.; Halawa, Intinilaiyana (LP. Ma'arif Janggan Magetan, 2024)
This research is motivated by the importance of preserving and integrating the local wisdom of the Toba Batak community in the national education system which is increasingly affected by the flow of globalization. Cultural values such as Dalihan Na Tolu, Hamoraon, Hagabeon, and Hasangapon have great potential in shaping students' character and identity. This study aims to identify, classify, and analyze the forms of local wisdom of Batak Toba and their relevance in the context of formal and non-formal education. This study analyzed in depth as many as 40 literature sources consisting of 35 journal articles (35 reputable international journals and 5 accredited national journals). These sources were selected based on inclusion criteria such as topic relevance, novelty (published in the last 10 years), The sources were selected based on inclusion criteria such as topic relevance, novelty (published in the last 10 years), and publisher credibility. The data collection technique is carried out through systematic searches using keywords in databases such as Google Scholar, Garuda, and DOAJ. Data analysis is carried out through the stages of identification, selection, classification, and thematic synthesis. The results of the study show that the local wisdom of Batak Toba includes life philosophy, oral traditions, traditional values, social systems, and environmental ethics that can be integrated in contextual learning and character education. These values are very relevant to support the implementation of the Independent Curriculum and Pancasila Student Profile. In addition to being a means of cultural preservation, this integration also strengthens inclusive and civilized multicultural education. Thus, the local wisdom of Batak Toba is a strategic source of educational value in the development of the Indonesian education system.